Dynamic field experiments in development economics: Risk valuation in Morocco, Kenya, and Peru - Lybbert, T.J.; Galarza, F.B.; McPeak, J.G.; Barrett, Christopher B.; Boucher, S.R.; Carter, S.; Chantarat, S.; Fadlaoui, A.; Mude, Andrew G. (Cambridge University Press, 2010)
The effective design and implementation of interventions that reduce vulnerability and poverty require a solid understanding of underlying poverty dynamics and associated behavioral responses. Stochastic and dynamic benefit streams can make it difficult for the poor to learn the value of such interventions to them. We explore how dynamic field experiments can help (i) intended beneficiaries to learn and understand these complicated benefit streams, and (ii) researchers to better understand how the poor respond to risk when faced with nonlinear welfare dynamics. We discuss and analyze dynamic risk valuation experiments in Morocco, Peru, and Kenya.